STUDI KOMPARASI PENDEKATAN HUKUM PADA PENGATURAN INSIDER TRADING DALAM KAITANNYA DENGAN PENEGAKAN DI DUNIA PASAR MODAL - Puspita Shara, Made Cinthya (LITIGASI, 2021)
The approach of fiduciary duty used in upholding capital market law in Indonesia implies on the imposition of crimes against insider trading becomes narrow. The obligation to prove the elements against the law to be able to prosecute the insider trading is also considered burdensome in providing justice. Insider trading is very likely to committed by parties who are not related to the company and to obtain information voluntarily. The weaknesses of the stipulation of legal approaches in Indonesia make it less viable to enforce material information on the capital market. Therefore, this study aims to understand the law enforcement that can guarantee security in the world of capital markets. This research will examine the use of the concept in Singapore which uses the concept of an information connected approach. In this concept, as the findings showed, Singapore uses a combination of approach to fiduciary duty and misappropriation. Based on this research, the results showed that the approach combining two possible actions of insider trading is a regulation that can provide more coerciveness to law enforcement in the capital markets. Therefore, it is necessary for Indonesia to carry out legal development by applying the misappropriation approach in the stipulations of insider trading in Indonesia. Keywords: Insider Trading, Legal Approach, Information.